Vegetative anatomical traits of Bulbostylis paradoxa (Spreng.) Lindm (Cyperaceae) - Rosalem, Patrícia Fernanda [UNESP]; Fidelis, Alessandra [UNESP]; Zanzarini, Vagner [UNESP]; de Camargos, Liliane Santos [UNESP]; Martins, Aline Redondo [UNESP] (Elsevier, 2025)
Bulbostylis paradoxa (Cyperaceae) is found in a range of environments experiencing distinct abiotic disturbances. The species shows a support organ common in Cyperaceae, called the caudex, whose morphoanatomical study may contribute to a deeper understanding of the species structural characteristics and their relationship to the environment. Therefore, here, we aimed to describe the anatomy and morphology of the vegetative organs of B. paradoxa to identify its distinctive structural characteristics. Plants were collected in the Cerrado tropical-savanna region of Central Brazil. Samples were fixed in FAA 70 %, dehydrated in an ethyl alcohol series, and embedded in historesin. Slides were stained with toluidine blue prior to histochemical and Scanning Electron Microscopy analysis. The presence of lignified cell walls in the epidermis and accessory cells was a major feature. Additionally, lignified cell walls were found in the sheaths of the vascular bundles, strongly indicating the presence of tissues that confer resistance and protection. Histochemical tests revealed the presence of starch grains and pectic substances in all vegetative organs, whereas phenolic compounds were found only in caudex cells. Fires are a frequent occurrence in the sampling area, and we observed that fires consume the leaves but do not damage the roots or caudex tissues. Further, tector trichomes present in the leaf sheaths of the caudex apex also contribute to the protection of the stem structure during a fire event. These results show that B. paradoxa has adaptive anatomical and morphological characteristics intrinsically related to the surrounding.
Keywords: Bulbostylis paradoxa; Caudex; Lignin; Monocotyledons; Phenolic compounds; Starch